Analysis of the Normative Framework Regarding the Cadastral System and of Cadastral Disputes in Republic of Moldova - Stahi, Tatiana; Robea, Mariana (Journal of Danubian Studies and Research, 2024)
Any reform, oriented towards radical changes in economic relations, first of all - property relations, is considered fundamental. The general specificity of the reforms that the Republic of Moldova is going through in the current period, refers to both the form and the content of the main fragment of economic relations - ownership, rule issued through the cadastral agency. And the development of the cadastral system is also considered one of the strategic national priorities in the future, considering the specific favorable characteristics of the country - the natural and socio-economic framework , historical traditions and the importance of regulating and protecting cadastral relations. The relevance of the study is argued by: the conceptual changes that have taken place in the content of the object of cadastral relations and of the material and procedural legislation applicable to the resolution of disputes when stars. Through a thorough and multilateral and not least critical analysis, the study constitutes an analysis of the cadastral system and cadastral disputes, both at the national and international level, it was also proposed to carry out a complex study of comparative legal analysis, and the appearance, the normative evolution of the cadastral system in the Republic of Moldova, as well as on the basis of the regulations of other countries. The study was based on the use of the methods of analysis, synthesis, deduction, comparison and interpretation.